W. Edwards Deming papers - Deming, W. Edwards (William Edwards), 1900-1993.
Correspondence, memoranda, reports, articles, speeches, lectures, interviews, reviews, books, writings, charts, notes, itineraries, awards, citations, musical scores, photographs, and other papers documenting Deming's government service at the U.S. Bureau of the Budget and Bureau of the Census; his academic positions at George Washington University, New York University, and the U.S. Dept. of Agriculture Graduate School; and, particularly, his career as a consultant in statistical studies and management in the United States and abroad. The collection reflects Deming's advocacy of the application of statistical quality control in industry and his work with motor freight, railroad, and telephone companies. Includes material relating to the influence of his ideas on Japan's economy following World War II and also on conditions in Great Britain, India, and Turkey. Other topics include his interest in music and trips to Greece in 1946 to observe elections there.
Organizations represented include the American Statistical Association and Nikkagiren (Union of Japanese Scientists and Engineers). Correspondents include A. C. Aitken, George A. Barnard, Raymond T. Birge, Harold French Dodge, Peter Ferdinand Drucker, Churchill Eisenhart, Sir Ronald Aylmer Fisher, Newt Gingrich, Lee A. Iacocca, Ichiro Ishikawa, J. M. Juran, Maurice G. Kendall, Ken'ichi Koyanagi, Gregory Lidstone, P. C. Mahalanobis, Jawaharlal Nehru, Jerzy Neyman, E. S. Pearson, Karl Pearson, H. Ross Perot, Dan Quayle, Ronald Reagan, Robert B. Reich, Walter A. Shewhart (Bell Telephone Laboratories), Pandurang Vasudeo Sukhatme, L. H. C. Tippett, John Wilder Tukey, W. Allen Wallis, and John Wishart.
Statistician and educator; died 1993.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aitken, A. C. -- 1895- -- Correspondence; Barnard, George A. -- Correspondence; Birge, Raymond T. -- 1887- -- Correspondence; Dodge, Harold French, -- 1893- -- Correspondence; Drucker, Peter F. -- 1909-2005 -- Correspondence; Eisenhart, Churchill -- Correspondence; Fisher, Ronald Aylmer, -- Sir, -- 1890-1962 -- Correspondence; Gingrich, Newt -- Correspondence; Iacocca, Lee A. -- Correspondence; Ishikawa, Ichirō -- Correspondence; Juran, J. M. -- 1904-2008 -- Correspondence; Kendall, Maurice G. -- 1907-1983 -- Correspondence; Koyanagi, Ken'ichi -- Correspondence; Lidstone, Gregory -- Correspondence; Mahalanobis, P. C. -- 1893-1972 -- Correspondence; Nehru, Jawaharlal, -- 1889-1964 -- Correspondence; Neyman, Jerzy, -- 1894-1981 -- Correspondence; Pearson, E. S. -- 1895-1980 -- Correspondence; Pearson, Karl, -- 1857-1936 -- Correspondence; Perot, H. Ross, -- 1930- -- Correspondence; Quayle, Dan, -- 1947- -- Correspondence; Reagan, Ronald -- Correspondence; Reich, Robert B. -- Correspondence; Shewhart, Walter A. -- 1891-1967 -- Correspondence; Sukhatme, Pandurang Vasudeo, -- 1911- -- Correspondence; Tippett, L. H. C. -- 1902- -- Correspondence; Tukey, John Wilder, -- 1915- -- Correspondence; Wallis, W. Allen -- 1912- -- Correspondence; Wishart, John, -- 1898-1956 -- Correspondence; American Statistical Association; Bell Telephone Laboratories; George Washington University -- Faculty; Graduate School, USDA -- Faculty; New York University -- Faculty; Nikkagiren; United States. -- Bureau of the Budget; United States. -- Bureau of the Census; Elections -- Greece -- 1946.; Freight and freightage -- Quality control; Management; Music; Quality control; Railroads -- Quality control; Statistics; Telephone companies -- Quality control; Great Britain -- Economic conditions -- 1945-1964.; India -- Economic conditions -- 1945-; Japan -- Economic conditions -- 1945-; Turkey -- Economic conditions -- 1945-; Educators; Statisticians